2014
DOI: 10.4103/0974-2700.125638
|View full text |Cite
|
Sign up to set email alerts
|

Migrating bullet: A case of a bullet embolism to the pulmonary artery with secondary pulmonary infarction after gunshot wound to the left globe

Abstract: Bullet embolism is a rare phenomenon following gunshot injuries. We present a case of a 25-year-old male who sustained a gunshot wound to his left globe with the bullet initially lodged in his right transverse sinus. The bullet ultimately embolized to a left lower lobe pulmonary artery resulting in a pulmonary infarct. A discussion of select prior cases, pathophysiology, and management strategies follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 8 publications
5
32
0
Order By: Relevance
“…Many authors reported cases of venous BE mostly managed by endovascular techniques [10][11][12][13] while others were managed by open surgery [14][15][16][17][18][19][20] or nonoperatively [5,21]. Open surgery was either used as a primary procedure or after failure of endovascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors reported cases of venous BE mostly managed by endovascular techniques [10][11][12][13] while others were managed by open surgery [14][15][16][17][18][19][20] or nonoperatively [5,21]. Open surgery was either used as a primary procedure or after failure of endovascular intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography showing a 5 mm bullet that embolized to the left lower lobe pulmonary artery, causing a pulmonary infarction (a = lung window images; b = bone window images). Source: Duke et al [1]. Images used under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike License (CC BY-NC-SA), which permits noncommercial use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Bullet or Projectile Embolismmentioning
confidence: 99%
“…Both traumatic and iatrogenic foreign intravascular object emboli (FIOE) have been described in the literature [1][2][3]. Traumatic bullet or "projectile" emboli (BPE) are mostly secondary to bullets or bullet fragments [1,4,5], with various types of shrapnel contributing to a smaller number of total cases [6]. In general, smaller caliber projectiles such as shot gun pellets are among the most common BPEs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Bullet embolism (BE) is a term used to describe the intravascular movement of a projectile distant to the entry site 1. Cranial BE is rare and mostly observed in the anterior circulation, which is thought to be due to the diameter and flow of the internal carotid artery (ICA) 2 3.…”
Section: Introductionmentioning
confidence: 99%